Performing autobiography: Narrating a life as activism - Powell, Katrina M. (Palgrave Macmillan, 2021)
Performing Auto/biography: Narrating a Life as Activismanalyzes the rhetorical strategies employed in five authors' auto/biographical texts, examining their representations of identities and the public implications of writing individual identity. Exploring the ways race, class, culture, ethnicity, gender, and sexuality might affect the form(s) in which writers choose to write (e.g., memoir, fictional autobiography, poetry), questions how autobiographers challenge notions of genre, truth, and representation. This builds on the argument that constructing identity is a Performing Autobiography performance, one that can simultaneously use and subvert traditional notions of rhetoric and genre. By examining the auto/biographical texts of Zora Neale Hurston, Audre Lorde, Dorothy Allison, Joyce Johnson, and Shirley Geok-lin Lim together, the book theorizes self-representation and genres as rhetorical performances, and therefore their texts can be seen as "performative auto/biography"–transgressive archives where readers are asked to consider their own identities and act accordingly. In doing so, this book contributes to growing theories in feminist rhetorics and auto/biography studies, arguing that these performative genres advocate for life narratives as political and social activism.
Keywords: approches et analyses; archives; arts; autobiographie; discipline; histoire et politique; intersectionnalité; ressource en ligne; thématiques; études littéraires